Efektivitas Tawas Hasil Olahan Limbah Aluminium Terhadap Penyerapan Logam Alkali Tanah dengan Metode Gravimetri - Nelius Harefa; Gayus Sadarman Tafonao; Desy Lisdawaty Sinaga (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2019)
Waste is one of the major problems in Indonesia. Waste continues to increase every year. The two major contributors of waste are plastic and metal processed waste. The two kinds of waste are undegradable. Therefore, the most appropriate solution in handling these kinds of waste is to recycling or converting. One of the efforts that can be made to waste aluminum is beverage packaging, namely by turning it into alum. Alum is commonly used as a water purifier, especially water containing calcium and magnesium metals which are often called hard water. The method used is gravimetric methods. Based on research data, alum can absorb calcium metal with an effectiveness level of 42.25% and magnesium metal with an effectiveness level of 64.12%. Keywords: alum, calcium metal, magnesium metal, gravimetric methods